Continued Pretraining on Mathematical Corpora Enhances Adversarial Robustness in Small Decoder-Only Models - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: Does continued pretraining on mathematical corpora improve robustness against adversarial perturbations in competition-level math problems for small decoder-only models. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.5/10. This report is a machine-generated literat
Machine-generated literature synthesis.